2009
DOI: 10.1007/s00520-009-0685-4
|View full text |Cite
|
Sign up to set email alerts
|

Parental stress before, during, and after pediatric stem cell transplantation: a review article

Abstract: Goals of work Pediatric stem cell transplantation (SCT) is a stressful treatment for children with relapsed or high-risk malignancies, immune deficiencies and certain blood diseases. Parents of children undergoing SCT can experience ongoing stress related to the SCT period. The aim of this article was to present a literature review of articles on parental distress and adaptation before, during, and after SCT and to identify risk and protective factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 38 publications
(96 reference statements)
2
46
0
1
Order By: Relevance
“…Despite these advancements, pediatric HSCT remains a physically and emotionally demanding treatment for children and their families. Transplantationrelated morbidity and mortality remain substantial [1], and research into the psychosocial impact of pediatric HSCT has demonstrated high levels of family distress despite standard institutional supportive care interventions [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advancements, pediatric HSCT remains a physically and emotionally demanding treatment for children and their families. Transplantationrelated morbidity and mortality remain substantial [1], and research into the psychosocial impact of pediatric HSCT has demonstrated high levels of family distress despite standard institutional supportive care interventions [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…3 Little is known regarding psychological distress for parents, particularly for fathers, whose children undergo SCT. [4][5][6][7] A small cross-sectional study suggested that mothers of children who undergo SCT experience greater distress than fathers. 6 Retrospective studies suggest that parental distress is highest before the transplant.…”
Section: Introductionmentioning
confidence: 99%
“…More longitudinal studies are needed to better understand mothers' and fathers' psychological distress and related factors after pediatric SCT. 7 This longitudinal study examined maternal and paternal psychological distress, measured by symptoms of depression and anxiety, before, and 1 and 2 years post SCT. These measures were used successfully in our previous work with this population and with parents of children with cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] In addition to interventions like radio-and chemo-therapy, some children must also endure HSCT, which entails repeated procedures, pain and isolation. It has previously been reported that the child's illness and treatment have an important role in the parents' lives for many years.…”
Section: Introductionmentioning
confidence: 99%